LEGAL STATUS OF ADVISORS IN THE FIELD OF INTELLECTUAL PROPERTY RIGHT IN THE UNITED KINGDOM - Kmetyk, Khrystyna (Proceedings of National Aviation University (archive), 2017)
Purpose: to research the legal status of advisors in the field of intellectual property right in the United Kingdom. In this article an author distinguishes and gives a legal description of the types of advisors in the field of intellectual property right in the United Kingdom. The main provisions of the Rules of Conduct for Patent Attorneys, Ttrade Mark Attorneys and Other Regulated Persons (2015) are considered. Methods: to analyse the legal status of advisors in the field of intellectual property right in the United Kingdom the method of induction, systematic approach, formal legal methods were used. Results: this research provides an opportunity to broaden the understanding of the institute of advisors in the field of intellectual property right (in particular patent attorneys and trademark attorneys) in the UK and thus include this knowledge in domestic research on intellectual property right. Conclusions: the majority of types of advisors in the field of intellectual property right in the United Kingdom (patent attorneys, chartered patent attorneys, European patent attorneys, registered trademark attorneys and trademark attorneys, European trademark attorneys, etc.) is well-educated professionals in all areas of intellectual property and are able to advise on a wide range of technical and commercial issues in this field. The obtained results will have a positive impact on the reform of the institute of representatives in the field of intellectual property in Ukraine in order to ensure its effectiveness and relevance to the challenges of the present.